Gender-related differences in career development among gynecologic oncology surgeons in Europe. European Network of Young Gynecologic Oncologists’ Survey based data - Nikolova, Tanja; Bossart, Michaela; Kacperczyk-Bartnik, Joanna; Razumova, Zoia; Strojna, Alexandra; Bizzarri, Nicolò; Pletnev, Andrei; Gómez-Hidalgo, Natalia R.; Theofanakis, Charalampos; Lanner, Maximilian; Selcuk, Ilker; Shushkevich, Alexander; et al. (Frontiers in Oncology, 2022)
Gender-related differences in career development are well-known issues in various professions. An international survey on gender-related differences was performed among young gynecologic oncology surgeons in Europe to identify potential gender inequalities in career development. Material and methods: A survey on demographics, clinical and academic working environment, family/parenting, career development, salary and leadership was sent to all members of the European Network of Young Gynecologic Oncologists (ENYGO), which is a network within the European Society of Gynecologic Oncology (ESGO). Gynecologic oncology surgeons and obstetricians/gynecologists who actively work in this field in Europe were included in the study. Results: Responses were analyzed from 192 gynecologic oncology surgeons of whom 65.1% (125/192) were female (median age 37, IQR: 34 - 42) and 34.9% (67/192) were male (median age 38, IQR: 36 - 41). Male reported to perform a median of 15 and female a median of 10 operations per month (p = .007). Among female, 24.8% had a leadership position vs. 44.8% among male, crude OR = 2.46, 95% CI 1.31-4.62, p < .01. When stratifying for age under 41 and having children, 36.7% of male and 5.6% of female had a leadership position, adjusted OR 10.8, 95% CI 3.28-35.64, p < .001. A significantly higher proportion of female compared to male believed they earned less than their gender counterparts at the same clinical position and with same qualifications (30.4% vs. 2.5%, p < .001). There was not a statistically significant gender difference in the academic qualification PhD degree or professorship (p = .92 and p = .64, respectively). In the previous year, male published more peer-reviewed articles than female (median 3 vs. median 2; p = .017). Conclusion: This first comprehensive survey on gender-differences in gynecologic oncology in Europe revealed that there are gender gaps concerning several aspects during the critical time of career development in the young generation of gynecologic oncology surgeons. These gender gaps are particularly reflected by a lower rate of female leadership positions. ENYGO and ESGO are dedicated to work on solution to overcome the identified obstacles and to support closing gender gaps.